Transparency as Rupture: Open Data and the Datafied Society of Hong Kong - Hoyng, Rolien (AoIR Selected Papers of Internet Research, 2017)
This paper deals with Open Data and the datafication of governance in Hong Kong. It addresses contestations over “transparency” as a techno-political construction that is embodied in, and performed by, the infrastructures and techniques of data-centric governance. Transparency is a site of negotiating distributions of cognition and perception in the context of transformations of citizenship and governance in the datafied society. I specifically inquire into the infrastructures, protocols, techniques, and practices of Open Data, which promises to simultaneously enhance government accountability and stimulate data-driven “smart” governance. Accordingly, I look at techno-political organizations of data and data infrastructures that support particular modes and distributions of cognition and perception (Halpern 2014; Hayles 2014; Kitchin 2014), which I distinguish as two data regimes respectively revolving around “representation” and “prediction.” I furthermore situate these issues in the larger institutional and political context of Hong Kong. The relevance of locating this case study in Hong Kong is that Hong Kong brands itself as an ICT Hub and ranks rather highly on smart city indexes. Yet at the same time the process of adapting Open Data is (structurally) incomplete, disruptive, and disrupted in the encounter with residual rationalities of statecraft. Hong Kong as a Special Administrative Region of China helps us think about datafication and Open Data in relation to the transgressive processes of accommodating neoliberalism through an array of exceptions (Ong 2006). Yet the case of Hong Kong also provides a glimpse of the possibilities for intervention and Open Data activism.